2006
DOI: 10.1517/17425255.2.6.847
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane X receptor and natural products: beyond drug–drug interactions

Abstract: The pregnane X receptor (PXR, NR1I2) is a member of the nuclear receptor superfamily that is activated by a myriad of compounds and natural products in clinical use. Activation of PXR represents the basis for several clinically important drug-drug interactions. Although PXR activation has undesirable effects in patients on combination therapy, it also mediates the hepatoprotective effects exhibited by some herbal remedies. This review focuses on PXR activation by natural products and the potential therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 65 publications
0
44
0
1
Order By: Relevance
“…Highly expressed in the liver and intestinal epithelium, the PXR has been previously characterized as a master regulator of xenobiotic metabolism and clearance (Watkins et al, 2002;Staudinger et al, 2006;Shukla et al, 2011;Dou et al, 2013;Pondugula and Mani, 2013). Acting as a sensor of exogenous chemicals, the PXR's activation leads to the expression of a variety of target genes related to detoxification and efflux pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Highly expressed in the liver and intestinal epithelium, the PXR has been previously characterized as a master regulator of xenobiotic metabolism and clearance (Watkins et al, 2002;Staudinger et al, 2006;Shukla et al, 2011;Dou et al, 2013;Pondugula and Mani, 2013). Acting as a sensor of exogenous chemicals, the PXR's activation leads to the expression of a variety of target genes related to detoxification and efflux pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These include synthetic drugs of various therapeutic classes and diverse chemical structures, naturally occurring compounds, endogenous substances, including bile acids and vitamins, and environmental toxicants. In contrast to the volume of information on PXR activation by single chemical entities (12,16), considerably less is known about the effect of complex chemical mixtures, such as herbal medicines, on PXR activity (26). St. John's wort was the first herbal medicine shown to activate PXR (13,14).…”
Section: Pregnane X Receptormentioning
confidence: 99%
“…The scope has widened to include many natural products after it was demonstrated that gugulipid, kava kava, Coleus forskolii, Hypoxis, Sutherlandia, Sweet Wormwood, Schisandra chinensis, and Glycyrrhiza are activators of PXR-mediated target gene expression [58] . PXR is also activated by vitamins E (tocopherol) and K2 [59,60] .…”
Section: Implications Of Pxr In Ddismentioning
confidence: 99%